Tanaman Obat Keluarga (Toga) Di Nagari Koto Baru Kecamatan Sungai Pagu Kabupaten Solok Selatan - Febriani, Revi; Nursyahra, Nursyahra; Maizeli, Annika (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Since ancient times, traditional medicine has been a natural form of treatment and is still evolving now.But few people are aware of how plants are used in traditional medicine.There is still a lack of public awareness regarding the therapeutic qualities of plants in the family.Finding the different plant species and family components that are employed as therapeutic plants in traditional medicine is the goal of the research.This study employs descriptive methodology and is research-based.In addition to conducting interviews and observations using purposive sampling approaches, the research involved direct observation, the gathering of medicinal plants at the location, and observations.Instead of sampling at random, researchers in the field were observed and recorded.The investigation yielded 57 species of medicinal plants that the residents of Nagari Koto Baru Sungai Pagu District, South Solok Regency, including 36 families used as components for traditional medicine.